The role of the interaction between macrophages and mesangial cells in the progression of IgA nephropathy - UTSUNOMIYA, Yasunori; ABE, Aya (Nihon Jinzo Gakkai shi, 1996)
IgA nephropathy is the most common form of glomerulonephritis in the world. Approximately, 20 to 30% of IgA nephropathy patients progress to end stage renal failure in 20 years. However, the mechanism (s) underlying the progression of IgA nephropathy has not been fully understood. The purpose of this study was to elucidate the role of the interaction betwen macrophages and mesangial cells in the progression of IgA nephropathy. Renal biopsy specimens from 40 patients with IgA nephropathy were examined to investigate the relationship between glomerular infiltration of mono cytes/ macrophages (Mo/ Mμ), glomerular expression of monocyte-specific chemoattractant, and their cliniopathological findings. The results led to the following conclusions. 1. The localization of Mo / Mμ within the glomerulus was identified as intracapillary or intramesangial by immuno cytochemistry with monoclonal antibody against CD68. 2. Close relationships between mesangial expressions of M-CSF and MCP-1, and mesangial localization of Mo/Mμ strongly suggested that mesangial production of these factors, in concert with glomerular ICAM-1 expression, enhances the recruitment and survival of Mo/Mμ in the mesangium. 3. It was suggested that Mo/Mμ localized in the mesangium play an important role in the progression of IgAN through increasing the production of matrix by mesangial cells.